AJARAN TRI KAYA PARISUDHA SEBAGAI LANDASAN PENDIDIKAN NILAI MORAL DAN ETIKA DALAM MEMBENTUK KARAKTER ANAK - I PUTU GEDE PARMAJAYA (Purwadita : Jurnal Agama dan Budaya, 2017)
The development  of  Hindu religious  education  do to  prepare  humans Hindu quality, which is reflected through the ability to think, communicate and behave in accordance with the identity of Hindu religion which is based on the concept of tri kaya parisudha teachings. Think, speak, do what is good and true is a reflection of moral behavior is a universal human phenomenon as well as a characteristic that distinguishes man from animals. Animals do not have the awareness of good and bad things, and is not acceptable, appropriate and inappropriate is done primarily a  moral  imperative  that  the  law  must  be  keewajiban  man  to  do  good  deeds.  In  the  tri  kaya parisudhacontaining education moral and ethical values   are very deep, as taught in detail to the Hindus to control dasendria (ten senses) which sometimes can not be controlled by man in this life, as a result of the increasing complexity of temptation objects worldly always stimulating the human senses.